Pengaruh Motivasi Kerja dan Beban Kerja terhadap Kinerja Karyawan pada PT Bio Farma (Persero) Kota Bandung - Andina, Mourien Rahmalia; Luturlean, Bachruddin Saleh (Universitas Mataram, 2024)
One of the main goals of a business organization or company is to achieve profits, human resources are part of the key factor in achieving these goals. Therefore, companies need to have the ability to manage their human resources well in order to improve employee performance throughout the organization. This also applies to the company PT Bio Farma (Persero) Bandung City, which must have a quality workforce to be able to compete with other companies in the current competitive environment. One factor that can increase human resource productivity is efforts to increase work motivation and pay attention to employee workload. This research aims to find out whether work motivation and workload have an influence on the performance of employees of PT Bio Farma (Persero) Bandung City. In this research, the author used a quantitative approach method with descriptive research type. Sampling was carried out using the probability sampling method, with a simple random sampling type, and involved 95 employees as respondents. The data analysis techniques used are descriptive analysis and multiple linear regression analysis. The results of descriptive research show that work motivation, workload and employee performance are in the good category. Multiple linear regression analysis reveals that work motivation variables (X1) and workload (X2) have a significant and positive effect on employee performance (Y). The conclusion of this research is that work motivation and employee workload, both partially and simultaneously, have a positive and significant effect on the performance of PT Bio Farma (Persero) Bandung City employees.